Study of various numerical aspects of 3D-SPH for simulation of the dam break problem - Ghadimi,Parviz (2012)
Recently, the Smoothed Particle Hydrodynamics (SPH) method has been utilized as an effective tool for capturing details of the fluid flows. The Lagrangian nature of the SPH method facilitates the modeling of the free surface flows. In the present article, different numerical features of 3D-SPH are probed to find a set of options that can be used to achieve an accurate numerical simulation of the dam break problem. Several numerical techniques such as time stepping algorithm, filter density and viscosity treatment are considered as compiling options. Twelve sets of mentioned schemes are also chosen and the elevation of free surface flow is captured. The obtained results are compared against the experimental data existing in the literature. Finally, it is concluded that the Symplectic algorithm in conjunction with density filter and SPS turbulence model can be used to achieve the desired accurate numerical results.